Analysis of Rice Field Agribusiness System in Sidomulyo Village, East Wasile District, East Halmahera Regency - Haryati Lakamisi (Sangia Publishing, 2021)
This study aims to determine the agribusiness system, production costs, revenue, income, and feasibility of lowland rice farming in Sidomulyo village. The research location was chosen purposively and the sample was taken using the census sampling method, the number of samples taken was 44 respondents. The analysis technique used is descriptive analysis. The results showed that the lowland rice agribusiness system in Sidomulyo village had been running well starting from the upstream agribusiness subsystem in the form of providing production facilities for fertilizers, medicines, seeds and labor. The subsystem of lowland rice farming using the jajar legowo system includes land cultivation, nursery, planting, fertilizing, use of drugs to harvesting. The downstream subsystem of lowland rice farming includes post-harvest and marketing activities. The subsystem of supporting institutions consists of BP3K which routinely provides counseling guidance and cooperative institutions that provide financing loans for lowland rice farmers, production costs per 10,000 m2 in lowland rice farming are Rp. and rice farming income of Rp. 13,595,218, -. Lowland rice farming is feasible, this can be seen from the R/C value > 1.